Labor Productivity Analysis Using Productivity Rating and Time Study Methods: Analisis Produktivitas Tenaga Kerja Menggunakan Metode Productivity Rating Dan Time Study - Kristiana, Retna; Ridhwan Gilang Ramadhan (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2025)
Ability of all individuals and well-organized companies to produce goods or services is a broad definition of productivity. Following the field observation procedure, data analysis was carried out using time study and Productivity Ranking techniques. Research methodology helps in systematic data collection and application of facts to solve problems. For three weeks, observations were made on the beam and floor slab formwork work using a daily field observation form that had been made previously. Ensuring that the worker's actions are in accordance with the observation by providing a checklist and recording the observation findings in the form. Calculating the results of the observation presentation. The beam and floor slab formwork work is a type of visible work. Labor efficiency level with a total average of three weeks of all work utilities, or LUR value, is known to be 66.30% based on the analysis results. Since labor is considered to have achieved effective or satisfactory time if it exceeds the LUR value or worker utility factor above 50%, the labor efficiency level is functioning successfully or satisfactorily. For a 40 m2 beam formwork work, productivity measurements such as scaffolding installation activities require a worker coefficient of 0.0182 m2/OH worker per day.